Generalized Jacobian Weighted Modulus of Smoothness - Al-Dhahabi, Ahmad AbdulKarim; Almurieb , Hawraa Abbas (Iraqi Journal of Science, 2023)
The topic of modulus of smoothness still gets the interest of many researchers due to its applicable usage in different fields, especially for function approximation. In this paper, we define a new modulus of smoothness of weighted type. The properties of our modulus are studied. These properties can be easily used in different fields, in particular, the functions in the  Besov spaces   when